Inteligência competitiva: a gestão da informação como instrumento para ações estratégicas na empresa Extrafarma - GOMES, Helayne da Silva Cardoso (2017)
Competitive intelligence study in a pharmaceutical company, motivated by the highly competitive scenario, that need to generate advantageous strategies to make a good management. In order to reflect how competitive intelligence can contribute to strategic actions in Extrafarma company, it presents a theoretical basis for conceptualizing the structures of information management and competitive intelligence cycles according to Valentim (2006), Tarapanoff (2001) and others. It is an exploratory research through a quantitative and qualitative method, carried out through a case study, with the use of questionnaires for data collection. In addition, the competitive intelligence cycle model of Amaral et al. (2004) was adopted, composed of six steps, to evaluate the intelligence process of the Company studied. As a result, the information flow and outlook performance of Extrafarma, the intelligence sector and the way information was organized were identified. The Extrafarma competitive intelligence cycle was also presented, with the following steps: information requirement, planning, collection, analysis, dissemination and evaluation of information in order to obtain strategies and competitive advantages. The research demonstrates the importance of the effective performance of the intelligence sector in the Company's activities to generate support for short, medium and long-term decisions, in view of generate competitive advantage, creating or sustaining new strategies.